Effects of bed length of adsorbent and humid air flow rate on adsorption efficiency of silica gel - Junsirisikul, Kanokpakorn; W.Lothongkum, Anchaleeporn (Engineering and Applied Science Research, 2013)
The effects of bed length of adsorbent and humid air flow rate on adsorption efficiency of silica gel were studied. Humid air with 85% RH flowed through the fixed bed adsorption column packed with silica gel. The experiments were conducted at atmospheric pressure. The adsorption efficiency was studied by varying bed length of adsorbent by changing the amount of adsorbents, and humid air flow rate. The bed lengths of adsorbent were 1.50, 3.00, 7.50 and 15.50 cm. Humid air flow rates were 50, 150 and 250 Nl/h. From break through curve it was found that at the bed length of 1.50 cm with humid air flow rates of 50, 150 and 250 Nl/h, the adsorption efficiencies were 1.67, 0.75 and 0.00 min, respectively. At the bed length of 3.00 cm with humid air flow rates of 50, 150 and 250 Nl/h, the adsorption efficiencies were 10.00, 1.50 and 1.00 min, respectively. At the bed length of 7.50 cm with humid air flow rates of 50, 150 and 250 Nl/h, the adsorption efficiencies were 75.00 6.00 and 3.60 min, respectively. At the bed length of 15.50 cm. with humid air flow rates of 150 and 250 Nl/h, the adsorption efficiencies were 56.67 and 14.30 min. From the experimental results the adsorption efficiency of silica gel increased and humid air flow rate decreased.